Detection of Extracellular Traps in Canine Steroid-Responsive Meningitis-Arteritis - Wohlsein, Jan C.; Meurer, Marita; Neßler, Jasmin; Wohlsein, Peter; von Köckritz-Blickwede, Maren; Baumgärtner, Wolfgang; Tipold, Andrea (Frontiers in Veterinary Science, 2022)
Extracellular traps (ET) are DNA networks formed by immune cells to fight infectious diseases by catching and attacking pathogenic microorganisms. Uncontrolled ET-formation or impaired ET-clearance can cause tissue and organ damage. Steroid-responsive meningitis-arteritis (SRMA) represents an immune-mediated, presumably noninfectious, purulent leptomeningitis and fibrinoid-necrotising arteritis and periarteritis of young-adult dogs. Chronic and recurrent cases of SRMA are characterized by lymphohistiocytic inflammatory cell infiltration in the meninges and perivascular tissue. The current study aimed to identify extracellular traps in dogs with SRMA, a model for immune-mediated diseases in the central nervous system (CNS). Hematoxylin-eosin stained samples of two young dogs with chronic, recurrent SRMA were examined by light microscopy for characteristic lesions and consecutive slices of affected tissues were stained for detection of ETs by immunofluorescence microscopy using antibodies against DNA-histone-1-complexes, myeloperoxidase and citrullinated histone H3. Histology revealed purulent and lymphohistiocytic leptomeningitis (n = 2/2) with meningeal periarteritis (n = 2/2) and periadrenal located lymphohistiocytic periarteritis (n = 1). Extracellular DNA networks and inflammatory cell infiltrates of macrophages, neutrophil granulocytes and lymphocytes were detected in the subarachnoid space of the leptomeninx (n = 2/2) and perivascularly in meningeal (n = 2/2) as well as periadrenal vessels (n = 1/1). In summary, extracellular DNA fibers and attached ET-markers are detectable in affected pericascular and meningeal tissues of dogs suffering from SRMA. The proof of principle could be confirmed, that ETs are present in canine, inflammatory and non-infectious CNS diseases and possibly play a role in the pathogenesis of SRMA.